Quantitatively immunological characterization of mogamulizumab skin disorders in ATL patients - Asahi Ito; Yui Suzuki; Ayako Masaki; Shinichiro Yoshida; Hitoshi Suzushima; Shigeki Takemoto; Atae Utsunomiya; Toshihiko Ishii; Masanori Hiura; Takeshi Takahashi; Satoshi Yurimoto; Hiroshi Inagaki; et al. (Frontiers Media S.A., 2019)
Abstract Purpose Skin disorders demonstrate highly variable phenotypical and histopathological features. Mogamulizumab, a humanized anti‐CC chemokine receptor 4 monoclonal antibody indicated for the treatment of adult T‐cell leukemia‐lymphoma, has been shown to induce skin‐related adverse events in some patients, including rare cases of Stevens‐Johnson syndrome. Hence, we aimed to elucidate immunological primary reactions in skins of mogamulizumab by quantitatively comparing any patterns of other skin disorders. Methods We quantitatively analyzed Foxp3+, CD8+, CD4+, granzyme B+, CD56+, and macrophage‐derived chemokine‐positive cells, and compared the results with trends observed in other inflammatory skin disorders such as psoriasis vulgaris, atopic dermatitis, and lichen planus. The analysis was separately performed in dermis, basement membrane, or epidermis of skins. Results Foxp3+/CD8+ cell ratio in dermis and basement membrane of mogamulizumab‐emergent skin disorders was significantly lower compared with those of the other skin disorders. In inflammatory skins, the more the number of CD8+ cells were infiltrated, the more the number of Foxp3+ cells were prone to be infiltrated, but not in mogamulizumab‐emergent skin disorders. No significant difference between all of the other skin disorders was observed in other immunological markers. Conclusion The low Foxp3+/CD8+ cell ratio of skins is the underlying reason for mogamulizumab‐emergent skin disorders.